(untitled) (Journal of Mechanical Engineering, 2009)
To avoid surface distortion and to improve tool life, machining of alloy steel and other hard materials under high speed-feed condition requires instant heat transfer from the work-tool interface where the intensity of cutting temperature is the maximum. Conventional cooling is completely unable and other special techniques like MQL and cryogenic cooling are not suitable in context of product quality and cost effectiveness. Supply of high-pressure coolant (HPC) with high velocity may provide the best control to reduce cutting temperature and tool wear as well as increase tool life. This paper deals with an experimental investigation on the effect of high-pressure coolant on temperature, tool wear, surface roughness and dimensional deviation in turning 42CrMo4 steel by uncoated carbide inserts and comparing it with dry condition. It is observed that the cutting temperature and tool wear is reduced, tool life is increased, surface finish is improved, and dimensional deviation is decreased with the use of high-pressure coolant. Keywords: High-pressure coolant (HPC), Alloy steel, Temperature, Wear and Product quality. doi:10.3329/jme.v39i2.1849 Journal of Mechanical Engineering, Vol. ME39, No. 2, Dec. 2008 71-77